Public Value Public Services at R. Ali Manshur Jatirogo Regional Hospital - Sunmainah, Sunmainah; Suprastiyo, Ahmad; Swasanti, Ida (Publik : (Jurnal Ilmu Administrasi), 2023)
Public value is a popular way to evaluate the effectiveness and efficiency of public services. This research aims to describe the public value of public services at R. Ali Manshur Jatirogo Regional Hospital. This research uses descriptive research with qualitative data analysis techniques. The technique for determining informants uses Purposive Sampling and Snowball Sampling. The focus of this research is described according to public value theory which consists of legitimacy and support, operational capabilities, and substantial value. Data collection techniques were obtained through observation, in-depth interviews, and documentation. Research data was analyzed using Miles and Huberman data analysis techniques using data reduction, simplification, abstraction, and data transformation. Based on the research results, it was found that the public services of R. Ali Manshur Jatirogo Regional Hospital have largely fulfilled the elements of public value theory. However, there are still shortcomings, such as the absence of blood bank services and a family waiting room which is still in progress. The R. Ali Manshur Jatirogo Regional Hospital always tries to make improvements to these deficiencies. However, in several cases, the researchers did not receive sufficient information from R. Ali Manshur Regional Hospital. So, it can be concluded that there is still a little lack of openness in certain matters, but it can be said that public services at R. Ali Manshur Jatirogo Hospital have quite good public value.